Pre-service teachers and socio-scientific inquiry: Opportunities and challenges - Knippels, M.C.P.J.; van Harskamp, M.; Verhoeff, R.P.; Postma, P.A. (ESERA, 2017)
This paper presents the results of a teacher training program aiming to enable pre-service teachers to engage secondary education students in Socio-Scientific Inquiry-Based Learning (SSIBL). In SSIBL – an approach developed within the European project PARRISE – students formulate questions about socioscientific issues and address these by integrating social and scientific inquiry. Socio-scientific inquiry stimulates students to form an opinion in which knowledge is balanced with social values and different stakeholder perspectives. In addition, students are asked to formulate solutions which help to enact change in a social environment. The developed teacher education program to promote teaching science using SSIBL, consisted of two 1,5 hour face-to-face training sessions and a take-home assignment to design a SSIBL lesson. A total number of 80 pre-service teachers (PSTs) from various science disciplines were involved. Qualitative methods were used to evaluate the SSIBL framework as interpreted by the PSTs and consisted of classroom observations, collection of lesson designs and a questionnaire. Results from the evaluation of the training program indicate PSTs experience the SSBL-approach as being promising in serving learning goals as critical thinking and reflective citizenship, which are considered to be important for contemporary science education. Additionally, PSTs regard the increased level of relevance of their subject for the students as a positive effect of SSIBL. Reported challenges include available time in the science curriculum and managing guidance and openness at the same time during the inquiry process.
Keywords: socioscientific issues; pre-service teacher education; values in science education